2009
DOI: 10.1016/j.bbrc.2008.11.109
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of constitutively activated ERK signaling enhances cytotoxicity of microtubule-destabilizing agents in tumor cells

Abstract: The extracellular signal-regulated kinase (ERK) signaling pathway is constitutively activated in many human tumor cell types. Given the cytoprotective role of this pathway, we examined whether its specific blockade might sensitize human tumor cells to the induction of apoptosis by various anticancer drugs. Although blockade of ERK signaling alone did not induce substantial cell death, it resulted in marked and selective enhancement of the induction of apoptosis by microtubule-destabilizing agents in tumor cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
2
14
0
Order By: Relevance
“…The efficacy of these drug combinations was greater than that of the combination of ERK pathway and PI3K-Akt pathway inhibitors. We have previously shown that blockade of the ERK pathway [26] or the PI3K-Akt pathway [27] enhances the induction of apoptosis by microtubule-destabilizing agents in tumor cells in which the respective signaling pathway is constitutively activated. Co-administration of a cytostatic signaling pathway inhibitor, such as a MEK inhibitor or a PI3K inhibitor, might thus represent a means to achieve safer anticancer strategies through lowering the required dose of cytotoxic anticancer drugs such as HDAC inhibitors or microtubule-destabilizing agents in a wide variety of cancer cells, including those resistant to EGFR or Abl TKIs.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of these drug combinations was greater than that of the combination of ERK pathway and PI3K-Akt pathway inhibitors. We have previously shown that blockade of the ERK pathway [26] or the PI3K-Akt pathway [27] enhances the induction of apoptosis by microtubule-destabilizing agents in tumor cells in which the respective signaling pathway is constitutively activated. Co-administration of a cytostatic signaling pathway inhibitor, such as a MEK inhibitor or a PI3K inhibitor, might thus represent a means to achieve safer anticancer strategies through lowering the required dose of cytotoxic anticancer drugs such as HDAC inhibitors or microtubule-destabilizing agents in a wide variety of cancer cells, including those resistant to EGFR or Abl TKIs.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, specific interruption of the cytoprotective ERK pathway by MEK inhibitors has been proposed as a means to enhance the lethal actions of cytotoxic anticancer agents through a shift in the balance between pro-and anti-apoptotic signaling. 17) Consistent with this notion, blockade of the ERK pathway by MEK inhibitors markedly enhances the cytotoxicity of several cytotoxic anticancer agents in tumor cells in which the ERK pathway is constitutively activated; these agents include microtubule-destabilizing agents 14,18) and histone deacetylase (HDAC) inhibitors. 19,20) MEK inhibitors (PD98059, PD184352, PD0325901) markedly and selectively enhance the induction of cell death by microtubule-destabilizing agents (vincristine, vinorelbine, TZT-1027) in a variety of tumor cell lines in which the ERK pathway is constitutively activated (HT-29 and TCO cells with Raf activation; HT1080, A549, and T24 cells with Ras activation; H1650, PC-9, and II-18 cells with EGFR activation), but not in tumor cells in which the ERK pathway is not activated (HeLa-S3, PC3, Colo320 cells) (Fig.…”
Section: Blockade Of Constitutively Activated Erk Pathway Enhances Thmentioning
confidence: 87%
“…2B, left and 2C). 14) Importantly, this effect of MEK inhibitors on cell death induction by microtubule-destabilizing agents is most pronounced at low concentrations of the latter drugs; under such conditions, microtubule-destabilizing agents by themselves exhibit only a small cytotoxic effect in the cells (Fig. 2B, right).…”
Section: Blockade Of Constitutively Activated Erk Pathway Enhances Thmentioning
confidence: 94%
“…However, blockade of the ERK pathway by itself was mostly cytostatic, rather than cytotoxic, resulting in only a moderate induction of apoptosis in these tumor cells (9). Thus, although PD184352 or AZD6244 totally suppressed the proliferation of T24 human bladder carcinoma cells in culture (11) or that of HT-29 human colon adenocarcinoma or BxPC3 human pancreatic cancer xenografts in vivo (12), respectively, these tumor cells remained viable and resumed proliferation after removal of the inhibitor or cessation of drug administration. Recent clinical studies of MEK inhibitors in patients with advanced cancers showed that, although PD184352 or AZD6244 achieved target inhibition at well-tolerated doses, these drugs alone exhibited insufficient antitumor activity (13,14).…”
mentioning
confidence: 97%
“…We have recently shown that blockade of the ERK pathway by PD98059 or PD184352 markedly enhanced the induction of apoptosis by microtubule-destabilizing agents, including vinorelbine and TZT-1027, in a variety of tumor cells with aberrant ERK pathway activation in vitro (11). We have now extended our in vitro findings and shown that PD184352-mediated blockade of the ERK pathway enhanced the induction of apoptosis by TZT-1027 in HT-29 xenografts in vivo as well as markedly potentiated the therapeutic efficacy of TZT-1027 or vinorelbine in HT-29 or HT1080 xenografts.…”
mentioning
confidence: 99%